1978
DOI: 10.1071/pp9780651
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies on the Proteins From Seeds of Lupinus angustifolius L.

Abstract: The seeds of 99 genotypes of L. angustifolius were examined by electrophoresis on cellulose acetate and found to contain two major salt-extracted globulins, conglutins α and β, and a third minor globulin, conglutin γ. Dissociation with sodium dodecyl sulfate and electrophoresis on polyacrylamide gel showed variation in the number, proportion and molecular size of the subunits which constitute these proteins. This was confirmed by electrophoresis in polyacrylamide gel containing urea at acid pH. The globulins i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
3

Year Published

1980
1980
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 0 publications
0
16
0
3
Order By: Relevance
“…Estudo comparativo de 100 amostras de sementes de tremoço de diferentes variedades e procedentes de 12 diferentes países mostrou variações de 30 a 50% de proteína total; contendo 60% das amostras de 32 a 38% de proteína, enquanto 28% apresentavam teores entre 38-44% de proteína [7,44]. % N 2 x 6,25), sendo 43,42% de globulinas, 10,77% de albuminas, 0,49% de prolaminas e 16,29% de glutelinas [33].…”
Section: -Resultados E Discussãounclassified
See 2 more Smart Citations
“…Estudo comparativo de 100 amostras de sementes de tremoço de diferentes variedades e procedentes de 12 diferentes países mostrou variações de 30 a 50% de proteína total; contendo 60% das amostras de 32 a 38% de proteína, enquanto 28% apresentavam teores entre 38-44% de proteína [7,44]. % N 2 x 6,25), sendo 43,42% de globulinas, 10,77% de albuminas, 0,49% de prolaminas e 16,29% de glutelinas [33].…”
Section: -Resultados E Discussãounclassified
“…A observação da Figura 5 permite afirmar que a proteína é composta de subunidades na faixa de 20-70 kDa e que não há pontes dissulfeto na molécula. Esses resultados confirmam aqueles relatados por MELO et al [31] e BLAGROVE & GILLESPIE [7]. A recromatografia em coluna de Q-sepharose mostrou um único pico (resultados não mostrados).…”
Section: Digestibilidade Das Proteínas De Tremoçounclassified
See 1 more Smart Citation
“…G., unpublished) showed that conglutin 6 is present in each species, although rarely resolved from conglutin a by electrophoresis on cellulose acetate. Therefore, because Blagrove et al6,7 show no evidence either for very broad conglutin a bands or a fourth electrophoretic species, it is assumed that conglutin 6 was not precipitated by the salting-out procedure they used. Thus, it is not surprising that the 2s protein has attracted little attention although it represents both a significant proportion of the total protein and up to 75% of the sulphur amino acids in the globular protein fraction of lupin seed.…”
Section: Blagrove Et Al ?'mentioning
confidence: 99%
“…After the pioneering studies by Joubert in South Africa during the 1950's (Joubert, 1955a(Joubert, , 1955b(Joubert, , 1955c(Joubert, , 1956(Joubert, , 1957 and others (Naismith, 1955;Petri et al, 1955;Gerritsen, 1956), an interest in the isolation and characterization of lupin seed proteins was rekindled during the 1970's by B1agrove and Gillespie in Australia (Gillespie and Blagrove, 1974;Gillespie, 1975: Gillespie andB1agrove, 1975;Blagrove et ai., 1976: Elleman, 1977: Blagrove and Gillespie, 1978: Gillespic et al, 1978B1agrove et aI., 1980) and by Cerlctti and Duranti in Italy (Duranti and Cerletti. 1979).…”
Section: Historical Perspectivementioning
confidence: 94%